NEW ECONOMIC GEOGRAPHY AND ALTERNATIVE CONCEPTIONS OF PRODUCTIONAL AGGLOMERATION - Lischynskyj, Ihor (Journal of European Economy, 2017)
Essence of the term «agglomeration» is considered. The paradigm of «new economic geography» is presented in the aspect of different agglomeration forms. The alternative theories of agglomeration are analyzed.